2013
DOI: 10.5792/ksrr.2013.25.1.30
|View full text |Cite
|
Sign up to set email alerts
|

Results of Arthroscopic Partial Meniscectomy for Lateral Discoid Meniscus Tears Associated with New Technique

Abstract: PurposeTo introduce and evaluate the clinical results of a new arthroscopic technique for partial meniscectomy of symptomatic lateral discoid meniscus using a knife.Materials and MethodsFrom March 2005 to October 2010, 60 knees of 58 patients underwent arthroscopic partial meniscectomies for lateral discoid meniscus. The average age was 28.9 years (range, 12 to 63 years), and average follow-up was 26 months (range, 8 to 72 years). In this procedure, using a No. 11 knife holder inserted through the high far ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…Many authors have reported good clinical results after partial meniscectomy with or without meniscus repair over short-, mid-, and long-term follow ups30,32,49,50,54,5659) (Table 1). Ahn et al32) reported in their study with a minimum 2-year follow-up (mean, 51 months) that arthroscopic partial meniscectomy with peripheral repair was effective for treating symptomatic discoid lateral menisci.…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…Many authors have reported good clinical results after partial meniscectomy with or without meniscus repair over short-, mid-, and long-term follow ups30,32,49,50,54,5659) (Table 1). Ahn et al32) reported in their study with a minimum 2-year follow-up (mean, 51 months) that arthroscopic partial meniscectomy with peripheral repair was effective for treating symptomatic discoid lateral menisci.…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…After the removal of duplicates and exclusion by screening the titles and abstracts, 31 records remained. After reviewing the full text, 15 studies [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] were finally included in the present study (►Fig. 1).…”
Section: Study Selectionmentioning
confidence: 99%
“…Only four studies 17,26,27,30 clearly reported the indication for surgery. Thirteen studies [16][17][18][19][20][22][23][24][25][26][27][28][29] provided relevant data about Ikeuchi grade, two studies 21,30 provided relevant data about IKDC score, and three studies 17,21,30 provided relevant data about Lysholm score for DLM patients. None of the included studies reported failure rate after surgery.…”
Section: Description Of Patients and Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…42 The therapy that is currently recommended in the case of a discoid meniscus is arthroscopic partial resection and reshaping. 43 The best results appear to be achievable when the partial resection and reshaping are completed soon after the first onset of symptoms. A root tear, which is similar to a complete radial tear, is a grave injury that leads to a complete loss of the meniscal function and therefore to the rapid development of OA; this is similar to the effects of a total meniscectomy.…”
Section: Indications For Meniscus Surgerymentioning
confidence: 99%